SPEECH ACT ANALYSIS OF TEACHER SPEECH IN THE CLASSROOM (Modern education and development, 2025)
This article examines the pragmatic functions of speech acts in teacher discourse within classroom settings. Through systematic analysis of authentic classroom interactions, we investigate how teachers employ different speech act categories—directives, expressives, representatives, commissives, and declarations—to facilitate learning, manage classroom behavior, and develop rapport with students. Our findings reveal that teachers predominantly utilize directive and representative speech acts, with significant variations across educational levels, subject matters, and pedagogical approaches. The research demonstrates that conscious attention to speech act deployment can enhance teaching effectiveness, student engagement, and classroom dynamics. Implications for teacher education programs and professional development are discussed, emphasizing the importance of pragmatic awareness in successful teaching practice.